A polyaniline modified cellulose nanofiber and a preparation method thereof

CN117988092BActive Publication Date: 2026-10-27HUAZHONG UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410150449.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-02
Publication Date
2026-10-27
Estimated Expiration
2044-02-02

AI Technical Summary

Technical Problem

[0005]本发明提供了一种聚苯胺修饰纤维素纳米纤维及其制备方法,有效解决了现有的合成方法存在的外加氧化剂,增加纯化样品难度以及形态尺寸无法控制的技术问题,同时提供了一种绿色高效、形态尺寸可控的聚苯胺修饰纤维素纳米纤维的制备方法

Benefits of technology

[0017]本发明提供的一种聚苯胺修饰纤维素纳米纤维及其制备方法,将苯胺单体与纳米纤维素水溶液混合,于酸性环境下加入NO3-源,得到混合溶液,采用电离辐照所述混合溶液,再进行后处理,得到聚苯胺修饰纤维素纳米纤维。本发明于酸性环境中促进苯胺质子化,进一步氧化得到阳离子自由基,从而引发聚合反应,而由于NO3-在酸性环境下具有较佳的氧化性,能够促使苯胺的氧化,故进一步提高聚苯胺的合成速率。通过电子束或γ射线辐射在纳米纤维素表面通过氢键作用力原位修饰纳米簇状聚苯胺。在不添加任何氧化剂的条件下,通过调节辐射能量的大小和辐射时间能够有效控制反应进程,采用电离辐射技术一步法合成聚苯胺修饰的纤维素纳米纤维。本发明提供的制备方法同步实现了聚苯胺的合成及对纳米纤维素的修饰,该方法绿色环保,快速高效,反应可以在很短的时间内进行,避免了传统化学合成方法繁琐的步骤,适用于大批量合成。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117988092B_ABST
    Figure CN117988092B_ABST
Patent Text Reader

Abstract

The application discloses polyaniline modified cellulose nanofiber and a preparation method thereof, and belongs to the field of ionizing radiation technology application. Aniline monomers are mixed with a nanocellulose solution, nitric acid is added, a mixed solution is obtained, the mixed solution is subjected to electron irradiation, and post-treatment is performed, so that polyaniline modified cellulose nanofiber is obtained. The polyaniline modified cellulose nanofiber is in-situ modified by nanocluster polyaniline on the surface of nanocellulose through hydrogen bond force by means of electron beam or gamma ray irradiation. Without adding any oxidant, the reaction process can be effectively controlled by adjusting the size of radiation energy and the radiation time. The polyaniline modified cellulose nanofiber is synthesized by using ionizing radiation technology in a one-step method. The method is green, environment-friendly, rapid and efficient, the reaction can be performed in a very short time, the cumbersome steps of a traditional chemical synthesis method are avoided, and the method is suitable for mass synthesis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ionizing radiation technology applications, specifically to a polyaniline-modified cellulose nanofiber and its preparation method. Background Technology

[0002] Polyaniline, as a conductive polymer material, has a wide range of applications. It can be used in the fabrication of electronic devices and sensors. For example, it can be used as a conductive electrode material in energy storage and conversion devices such as solar cells, supercapacitors, and lithium-ion batteries. It can also be used to fabricate sensors, such as gas sensors, humidity sensors, and biosensors, for detecting gases, humidity, and biomolecules in the environment. Furthermore, polyaniline possesses photocatalytic activity and can be used in fields such as photocatalytic decomposition of organic pollutants and water splitting for hydrogen production. However, polyaniline is a powdered polymer and cannot be directly molded for practical applications. Therefore, it is usually used as a filler or dopant to realize its properties.

[0003] Cellulose nanofibers are excellent carriers for polyaniline to exert its properties. Rich in polar groups such as hydroxyl groups, they can form abundant hydrogen bonds with aniline, which is a key reason why both can be modified or modified. Cellulose nanofibers are nanoscale cellulose materials composed of cellulose molecules. Cellulose is widely found in plant cell walls and is a natural polymer compound, one of the most abundant renewable biomass resources on Earth. With its high specific surface area, unique structural characteristics, natural origin, and biodegradability, cellulose nanofibers are considered a sustainable material with excellent mechanical properties and environmental friendliness. It can be used to prepare high-strength paper, textiles, films, coatings, nanocomposites, etc., and plays an important role in food packaging, drug delivery, and biosensors. Therefore, the production of polyaniline-modified cellulose nanofibers has significant practical implications.

[0004] Currently, most methods for synthesizing polyaniline are chemical oxidation methods, using oxidants such as ferric chloride and sodium persulfate, while other methods are less common. Chemical oxidation methods inevitably introduce salts into the system, increasing the difficulty of subsequent sample purification and also putting pressure on environmental protection. Furthermore, the size and degree of polymerization of the synthesized polyaniline are difficult to control, as they are significantly affected by the reaction temperature and the concentration of oxides. Therefore, the synthesis of nanoparticles using chemical oxidation methods still faces technical challenges. To address this, this invention provides polyaniline-modified cellulose nanofibers and their preparation method. Summary of the Invention

[0005] This invention provides a polyaniline-modified cellulose nanofiber and its preparation method, which effectively solves the technical problems of existing synthesis methods, such as the addition of external oxidants, which increases the difficulty of sample purification and the inability to control the morphology and size. At the same time, it provides a green, efficient, and morphology- and size-controllable method for preparing polyaniline-modified cellulose nanofibers.

[0006] The first objective of this invention is to provide a method for preparing polyaniline-modified cellulose nanofibers, characterized by comprising the following steps:

[0007] Aniline monomer was mixed with an aqueous solution of nanocellulose, and NO3 was added under acidic conditions. - The source was used to obtain a mixed solution, which was then irradiated with ionizing radiation and post-treated to obtain polyaniline-modified cellulose nanofibers.

[0008] In a preferred embodiment, the ionizing irradiation is electron beam or gamma-ray irradiation.

[0009] In a preferred embodiment, the ionizing irradiation dose rate is 1 Gy-10 kGy, and the irradiation dose is 30-100 kGy.

[0010] In a preferred embodiment, the concentration of the nanocellulose solution is 1.2 wt%, and the mass ratio of the aniline monomer to the nanocellulose is 2 to 16:1.

[0011] In a preferred embodiment, the aniline monomer and NO3 - The molar ratio of the sources is 2 to 10:1.

[0012] In a preferred embodiment, the acidic environment is provided by nitric acid, sulfuric acid, or hydrochloric acid, the concentration of which is 2–8 mol / L, and the concentration of the nanocellulose aqueous solution is 1.2 wt%, with the amount of nitric acid, sulfuric acid, or hydrochloric acid being equal to the volume of the nanocellulose solution.

[0013] As a preferred embodiment, the NO3 - The source includes nitrates, wherein the nitrates are sodium nitrate, potassium nitrate, silver nitrate, or copper nitrate.

[0014] As a preferred embodiment, the post-processing specifically involves: obtaining a crude product after electron irradiation, centrifuging the crude product at 5000-8000 rpm for 10-20 min, discarding the supernatant, and repeating the above centrifugation operation by alternately adding ethanol and water for 3 times to obtain a primary product, which is then dried at 30-50℃ for 6-12 h.

[0015] The second objective of this invention is to provide a polyaniline-modified cellulose nanofiber prepared by the above-described preparation method.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0017] This invention provides a polyaniline-modified cellulose nanofiber and its preparation method, which involves mixing aniline monomer with an aqueous solution of nanocellulose and adding NO3 under an acidic environment. - A mixed solution was obtained from a source, and then irradiated with ionizing radiation, followed by post-treatment to obtain polyaniline-modified cellulose nanofibers. This invention promotes the protonation of aniline in an acidic environment, further oxidizing it to generate cationic free radicals, thereby initiating the polymerization reaction. However, due to NO3... - It exhibits excellent oxidizing properties in acidic environments, promoting the oxidation of aniline and thus further increasing the synthesis rate of polyaniline. Nanocluster-like polyaniline is in-situ modified on the surface of nanocellulose via hydrogen bonding through electron beam or gamma-ray irradiation. Without adding any oxidant, the reaction process can be effectively controlled by adjusting the radiation energy and irradiation time, enabling a one-step synthesis of polyaniline-modified cellulose nanofibers using ionizing radiation technology. The preparation method provided by this invention simultaneously achieves the synthesis of polyaniline and the modification of nanocellulose. This method is green, environmentally friendly, rapid, and efficient; the reaction can be carried out in a very short time, avoiding the cumbersome steps of traditional chemical synthesis methods, and is suitable for large-scale synthesis. Attached Figure Description

[0018] Figure 1 This is a scanning electron microscope image of the polyaniline-modified cellulose nanofibers of Example 1 of the present invention;

[0019] Figure 2 This is a scanning electron microscope image of polyaniline-modified cellulose nanofibers from Example 2 of the present invention;

[0020] Figure 3 This is a scanning electron microscope image of the polyaniline-modified cellulose nanofibers of Example 3 of the present invention;

[0021] Figure 4 The thermogravimetric curves of the polyaniline-modified cellulose nanofibers of Example 1 and the unmodified cellulose nanofibers of Comparative Example 1 are shown in the figure.

[0022] Figure 5 The infrared spectra of the polyaniline-modified cellulose nanofibers of Example 1 and the unmodified cellulose nanofibers of Comparative Example 1 are shown in comparison. Detailed Implementation

[0023] To enable those skilled in the art to better understand and implement the technical solutions of this invention, the invention will be further described below with reference to specific embodiments and accompanying drawings. However, the embodiments described are not intended to limit the invention. Unless otherwise specified, the following test methods and detection methods are conventional methods; unless otherwise specified, the reagents and raw materials are commercially available.

[0024] To address the technical problems of existing chemical oxidation methods for synthesizing polyaniline, which introduce salts into the system, increasing the difficulty of subsequent sample purification, causing environmental pollution, and making it difficult to control the size and degree of polymerization of the synthesized polyaniline, this invention mixes aniline monomer with an aqueous solution of nanocellulose and adds NO3 under an acidic environment. - A mixed solution was obtained by irradiating the source with ionizing radiation, followed by post-treatment to obtain polyaniline-modified cellulose nanofibers. This invention utilizes electron beam or gamma-ray irradiation to in-situ modify nanoclusters of polyaniline onto the surface of nanocellulose via hydrogen bonding. Without adding any oxidizing agent, the reaction process is effectively controlled by adjusting the radiation energy and irradiation time, enabling a one-step synthesis of polyaniline-modified cellulose nanofibers using ionizing radiation technology.

[0025] Example 1

[0026] A method for preparing polyaniline-modified cellulose nanofibers includes the following steps:

[0027] S1. According to the mass ratio of aniline monomer to nanocellulose CNF 16:1, aniline monomer is mixed with CNF aqueous solution with a concentration of 1.2wt%, and HNO3 solution with a concentration of 2mol / L is added in an equal volume to the nanocellulose aqueous solution to obtain a mixed solution. The mixed solution is added to a polyethylene (PE) sample bag, sealed, and irradiated with an electron beam dose of 100kGy.

[0028] The polyethylene sample bag used in this invention not only has excellent radiation resistance, but also allows for easy penetration by electron beams, thereby ionizing and irradiating the composite solution.

[0029] S2, Place the irradiated sample in a centrifuge tube and centrifuge at 8000 rpm for 10 min. Discard the supernatant and repeat the centrifugation operation by alternately adding ethanol and water three times to wash away excess nitric acid, nitrates, and aniline. After washing, the primary product is obtained and placed in a vacuum oven at 40°C for 6 h to dry.

[0030] Example 2

[0031] A method for preparing polyaniline-modified cellulose nanofibers includes the following steps:

[0032] S1. According to the mass ratio of aniline monomer to CNF 8:1, aniline monomer is mixed with CNF aqueous solution with a concentration of 1.2wt%, and an equal volume of 2mol / L HNO3 solution is added. Then, copper nitrate is added according to the molar ratio of aniline monomer to nitrate 2:1 to obtain a mixed solution. The mixed solution is added to a polyethylene (PE) sample bag, sealed, and subjected to electron beam irradiation with a dose of 100kGy.

[0033] S2, Place the irradiated sample in a centrifuge tube and centrifuge at 8000 rpm for 10 min. Discard the supernatant and repeat the centrifugation operation by alternately adding ethanol and water three times to wash away excess nitric acid, nitrates, and aniline. After washing, the primary product is obtained and placed in a vacuum oven at 40°C for 6 h to dry.

[0034] Example 3

[0035] A method for preparing polyaniline-modified cellulose nanofibers includes the following steps:

[0036] S1. According to the mass ratio of aniline monomer to CNF 8:1, aniline monomer is mixed with CNF aqueous solution with a concentration of 1.2wt%, and an equal volume of 2mol / L HNO3 solution is added. Then, silver nitrate is added according to the molar ratio of aniline monomer to nitrate 2:1 to obtain a mixed solution. The mixed solution is added to a polyethylene (PE) sample bag, sealed, and subjected to electron beam irradiation with a dose of 100kGy.

[0037] S2, Place the irradiated sample in a centrifuge tube and centrifuge at 8000 rpm for 10 min. Discard the supernatant and repeat the centrifugation operation by alternately adding ethanol and water three times to wash away excess nitric acid, nitrates, and aniline. After washing, the primary product is obtained and placed in a vacuum oven at 40°C for 6 h to dry.

[0038] Example 4

[0039] A method for preparing polyaniline-modified cellulose nanofibers includes the following steps:

[0040] S1. According to the mass ratio of aniline monomer to CNF 16:1, aniline monomer is mixed with CNF aqueous solution with a concentration of 1.2wt%, and HNO3 solution with a concentration of 4mol / L is added in an equal volume to CNF aqueous solution to obtain a mixed solution. The mixed solution is added to a polyethylene (PE) sample bag, sealed, and subjected to electron beam irradiation with a dose of 100kGy.

[0041] S2, Place the irradiated sample in a centrifuge tube and centrifuge at 8000 rpm for 10 min. Discard the supernatant and repeat the centrifugation operation by alternately adding ethanol and water three times to wash away excess nitric acid, nitrates, and aniline. After washing, the primary product is obtained and placed in a vacuum oven at 40°C for 6 h to dry.

[0042] Example 5

[0043] A method for preparing polyaniline-modified cellulose nanofibers includes the following steps:

[0044] S1. According to the mass ratio of aniline monomer to CNF 16:1, aniline monomer is mixed with CNF aqueous solution with a concentration of 1.2wt%, and an 8mol / L HNO3 solution with a concentration equal to the volume of CNF aqueous solution is added to obtain a mixed solution. The mixed solution is added to a polyethylene (PE) sample bag, sealed, and subjected to electron beam irradiation with a dose of 100kGy.

[0045] S2, Place the irradiated sample in a centrifuge tube and centrifuge at 8000 rpm for 10 min. Discard the supernatant and repeat the centrifugation operation by alternately adding ethanol and water three times to wash away excess nitric acid, nitrates, and aniline. After washing, the primary product is obtained and placed in a vacuum oven at 40°C for 6 h to dry.

[0046] Example 6

[0047] A method for preparing polyaniline-modified cellulose nanofibers includes the following steps:

[0048] S1. According to the mass ratio of aniline monomer to CNF 16:1, aniline monomer is mixed with CNF aqueous solution with a concentration of 1.2wt%, and HNO3 solution with a concentration of 4mol / L is added in an equal volume to CNF aqueous solution to obtain a mixed solution. The mixed solution is added to a polyethylene (PE) sample bag, sealed, and subjected to electron beam irradiation with a dose of 30kGy.

[0049] S2, Place the irradiated sample in a centrifuge tube and centrifuge at 8000 rpm for 10 min. Discard the supernatant and repeat the centrifugation operation by alternately adding ethanol and water three times to wash away excess nitric acid, nitrates, and aniline. After washing, the primary product is obtained and placed in a vacuum oven at 40°C for 6 h to dry.

[0050] Example 7

[0051] A method for preparing polyaniline-modified cellulose nanofibers includes the following steps:

[0052] S1. According to the mass ratio of aniline monomer to CNF 16:1, aniline monomer is mixed with CNF aqueous solution with a concentration of 1.2wt%, and HNO3 solution with a concentration of 4mol / L is added in an equal volume to CNF aqueous solution to obtain a mixed solution. The mixed solution is added to a polyethylene (PE) sample bag, sealed, and subjected to electron beam irradiation with a dose of 60kGy.

[0053] S2, Place the irradiated sample in a centrifuge tube and centrifuge at 8000 rpm for 10 min. Discard the supernatant and repeat the centrifugation operation by alternately adding ethanol and water three times to wash away excess nitric acid, nitrates, and aniline. After washing, the primary product is obtained and placed in a vacuum oven at 40°C for 6 h to dry.

[0054] Example 8

[0055] A method for preparing polyaniline-modified cellulose nanofibers includes the following steps:

[0056] S1. According to the mass ratio of aniline monomer to CNF 16:1, aniline monomer is mixed with CNF aqueous solution with a concentration of 1.2wt%, and an equal volume of 4mol / L HNO3 solution is added. Then, potassium nitrate is added according to the molar ratio of aniline monomer to nitrate 2:1 to obtain a mixed solution. The mixed solution is added to a polyethylene (PE) sample bag, sealed, and subjected to electron beam irradiation with a dose of 100kGy.

[0057] S2, Place the irradiated sample in a centrifuge tube and centrifuge at 8000 rpm for 10 min. Discard the supernatant and repeat the centrifugation operation by alternately adding ethanol and water three times to wash away excess nitric acid, nitrates, and aniline. After washing, the primary product is obtained and placed in a vacuum oven at 40°C for 6 h to dry.

[0058] Example 9

[0059] A method for preparing polyaniline-modified cellulose nanofibers includes the following steps:

[0060] S1. According to the mass ratio of aniline monomer to CNF 2:1, aniline monomer is mixed with CNF aqueous solution with a concentration of 1.2wt%, and an equal volume of 4mol / L H2SO4 solution is added. Then, sodium nitrate is added according to the molar ratio of aniline monomer to nitrate 2:1 to obtain a mixed solution. The mixed solution is added to a polyethylene (PE) sample bag, sealed, and subjected to electron beam irradiation with a dose of 60kGy.

[0061] S2, Place the irradiated sample in a centrifuge tube and centrifuge at 8000 rpm for 10 min. Discard the supernatant and repeat the centrifugation operation by alternately adding ethanol and water three times to wash away excess nitric acid, nitrates, and aniline. After washing, the primary product is obtained and placed in a vacuum oven at 40°C for 6 h to dry.

[0062] Example 10

[0063] A method for preparing polyaniline-modified cellulose nanofibers includes the following steps:

[0064] S1. According to the mass ratio of aniline monomer to CNF 2:1, aniline monomer is mixed with CNF aqueous solution with a concentration of 1.2wt%, and an equal volume of 4mol / L HCl solution is added. Then, potassium nitrate is added according to the molar ratio of aniline monomer to nitrate of 10:1 to obtain a mixed solution. The mixed solution is added to a polyethylene (PE) sample bag, sealed, and subjected to electron beam irradiation with a dose of 60kGy.

[0065] S2, Place the irradiated sample in a centrifuge tube and centrifuge at 8000 rpm for 10 min. Discard the supernatant and repeat the centrifugation operation by alternately adding ethanol and water three times to wash away excess nitric acid, nitrates, and aniline. After washing, the primary product is obtained and placed in a vacuum oven at 40°C for 6 h to dry.

[0066] Example 11

[0067] A method for preparing polyaniline-modified cellulose nanofibers includes the following steps:

[0068] S1. According to the mass ratio of aniline monomer to CNF 2:1, aniline monomer is mixed with CNF aqueous solution with a concentration of 1.2wt%, and an equal volume of 4mol / L H2SO4 solution is added. Then, copper nitrate is added according to the molar ratio of aniline monomer to nitrate 6:1 to obtain a mixed solution. The mixed solution is added to a polyethylene (PE) sample bag, sealed, and subjected to electron beam irradiation with a dose of 60kGy.

[0069] S2, Place the irradiated sample in a centrifuge tube and centrifuge at 8000 rpm for 10 min. Discard the supernatant and repeat the centrifugation operation by alternately adding ethanol and water three times to wash away excess nitric acid, nitrates, and aniline. After washing, the primary product is obtained and placed in a vacuum oven at 40°C for 6 h to dry.

[0070] To further illustrate the technical effects of the present invention, comparative examples are also provided, as follows:

[0071] Comparative Example 1

[0072] The difference from Example 1 is that it does not undergo polyaniline modification and consists of simple cellulose nanofibers.

[0073] The morphology and properties of the polyaniline-modified cellulose nanofibers prepared in Examples 1-11 of this invention and the single cellulose nanofibers of Comparative Example 1 were characterized. Since the products prepared in Examples 1-11 have similar properties, the effects will be described using Examples 1-3 as examples. Specifically... Figures 1-5 As shown.

[0074] Figure 1 This is a scanning electron microscope (SEM) image of the polyaniline-modified cellulose nanofibers of Example 1 of the present invention. Figure 1 It can be seen that polyaniline nanoclusters were generated on the CNF surface after irradiation.

[0075] Figure 2 This is a scanning electron microscope (SEM) image of the polyaniline-modified cellulose nanofibers of Example 2 of the present invention. Figure 2 It can be seen that polyaniline nanoclusters were generated on the CNF surface after irradiation.

[0076] Figure 3 This is a scanning electron microscope (SEM) image of the polyaniline-modified cellulose nanofibers of Example 3 of the present invention. Figure 3 It can be seen that after irradiation, polyaniline nanoclusters and Ag particles were generated on the CNF surface.

[0077] Figure 4 This is a comparison of the thermogravimetric curves of the polyaniline-modified cellulose nanofibers of Example 1 and the unmodified cellulose nanofibers of Comparative Example 1. Figure 4 It can be seen that in a N2 atmosphere, the mass retention rate of polyaniline at 800℃ is about 60%, while that of CNF is close to 0. However, the mass retention rate of CNF after irradiation is about 15% at 800℃, which suggests that a new substance is generated and modifies CNF. This substance may be polyaniline.

[0078] Figure 5 This is a comparison of the infrared spectra of the polyaniline-modified cellulose nanofibers of Example 1 and the unmodified cellulose nanofibers of Comparative Example 1. Figure 5 It can be determined that: 1313cm -1 The peak at 1442 cm⁻¹ corresponds to the stretching vibration of CN. -1 1508cm -1 Corresponding to the vibration of the benzene ring, and 1641 cm -1 The formation of polyaniline can be explained by the vibration of C=N in the polyaniline quinone ring structure.

[0079] In summary, this invention utilizes electron beam or gamma-ray irradiation to in-situ modify nanoclusters of polyaniline on the surface of cellulose nanofibers via hydrogen bonding. Without adding any oxidizing agents, the reaction process can be effectively controlled by adjusting the irradiation energy and duration, enabling a one-step synthesis of polyaniline-modified cellulose nanofibers using ionizing radiation technology. The preparation method provided by this invention simultaneously achieves the synthesis of polyaniline and the modification of cellulose nanofibers. This method is green, environmentally friendly, rapid, and efficient, allowing the reaction to proceed in a very short time, avoiding the cumbersome steps of traditional chemical synthesis methods, and is suitable for large-scale synthesis.

[0080] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A method for preparing polyaniline-modified cellulose nanofibers, characterized in that, Includes the following steps: Aniline monomer was mixed with an aqueous solution of nanocellulose, and nitrate was added under an acidic environment to obtain a mixed solution. The mixed solution was then irradiated with an electron beam and post-processed to obtain polyaniline-modified cellulose nanofibers. The nitrate is sodium nitrate, potassium nitrate, silver nitrate, or copper nitrate; The electron beam irradiation dose is 30~100 kGy; The mass ratio of aniline monomer to nanocellulose is 2~16:1; The molar ratio of aniline monomer to nitrate is 2~10:1; The acidic environment is provided by nitric acid, sulfuric acid, or hydrochloric acid, the concentration of which is 2-4 mol / L, and the concentration of the nanocellulose aqueous solution is 1.2 wt%, with the amount of nitric acid, sulfuric acid, or hydrochloric acid being equal to the volume of the nanocellulose aqueous solution. The post-processing specifically involves: obtaining a crude product after electron beam irradiation, centrifuging the crude product, discarding the supernatant, and repeating the centrifugation operation by alternately adding ethanol and water three times to obtain a primary product, which is then dried.

2. A polyaniline-modified cellulose nanofiber prepared by the preparation method of claim 1.

Citation Information

Patent Citations

  • The method of manufacturing electroconductive cellulose complex using radiation technology and electroconductive cellulose complex manufactured thereby

    KR102088796B1